ByzRev 08.2026.017: Veronica della Dora – Charalambos Dendrinos – Mark Guscin – David John Williams (eds.), Sacred Mobilities in Byzantium and Beyond: People, Objects and Relics (The Medieval Mediterranean 140). Leiden: Brill 2025 - Sprecher, Christopher (The Byzantine Review, 2026)
Veronica della Dora – Charalambos Dendrinos – Mark Guscin – David John Williams (eds.), Sacred Mobilities in Byzantium and Beyond. People, Objects and Relics (The Medieval Mediterranean 140). Leiden: Brill 2025. xiv + 360 pp. – ISBN 978-90-04-70158-8 (€ 150.70)